Nonunion of Supracondylar and Intercondylar Fracture of Femur Combined with Severe Hemophilic Arthropathy Treated with Condylar Constrained Total Knee Arthroplasty: A Case Report - Chiu-Yu Shih; Ing-Lin Chang; Chun-Hsiung Huang; Hsin-Yao Chen; Chih-Hui Chen; Cheng-Pu Hsieh; Hsuan-Yu Lin; Ming-Ching Shen (Formosan Journal of Musculoskeletal Disorders)
Hemophilic arthropathy and nonunion of distal femur fractures pose significant challenges for treating surgeons. When these conditions are combined, they create a complex pathology that can lead to the development of pseudoarthrosis, reduced bone stock, extensive fibrotic changes that cause adhesions, muscle contractures and atrophy, fixed bony deformities, and severe osteoporosis. Management of hemophilic arthropathy and nonunion of distal femur fractures requires careful consideration of preserving joint function, addressing instability resulting from nonunion, and mitigating further complications. One possible approach is the use of constrained condylar total knee arthroplasty (TKA). This surgical technique provides several advantages, including the ability to alleviate arthritic pain, improve knee function, address fracture nonunion, and expedite recovery of range of motion and ambulation while avoiding complications associated with nonweight-bearing periods and extended immobilization encountered after osteosynthesis procedures. We present a case report of a patient with severe hemophilic knee arthropathy and nonunion of the supracondylar and intercondylar fracture of the femur. This patient underwent successful treatment with condylar constrained TKA. To our knowledge, this is the first reported case in the literature that highlights the importance of continuing research on effective treatment modalities for patients with complex joint pathologies. This approach has the potential to significantly improve patient outcomes and improve patient quality of life.